As misérias do Habeas Corpus Coletivo - Temer, Pedro Pessoa (2023)
This text aims to study the Collective Habeas Corpus (or, as some may prefer, Habeas Class Action) from a procedural perspective. In the first chapter, starting from premises about mass society and the Habeas Corpus, it was established basic concepts for its analysis. In the second chapter, it was researched the interaction difficulties between the branches of collective and criminal process, including the existing interpenetration between civil and criminal proceedings. A distinction was made between the nature of the collective criminal process, when it is punitive (with restrictions), and the non-punitive nature (more accepted in the collective perspective), among which the focus of the research, the Collective Habeas Corpus, stands out. The use of collective seizure warrants was studied (counterpoint to the acceptance of the Collective HC) and, due to its relevance, measures within Inq 4.879/DF were examined. In the third chapter, it was tried to systematize the position of the Supreme Federal Court (STF) and Superior Court of Justice (STJ) regarding the Collective HC before the judgment of the HC number 143.641/SP, in 2018, with case studies, delimitation, and overcoming the (fake)problem of the "indeterminability" of the parties. Also in this second chapter, it was analyzed the main arguments that justify the jurisprudential shift around HC number 143.641/SP, in order to accept the writ in the collective modality. Regarding the doctrine, the research was divided among the doctrine of criminal procedure, constitutional doctrine, collective process doctrine, specific doctrine of Public Defenders, master's texts, doctoral theses, and articles that address the topic. In the fourth chapter, it was assessed the interactive dynamics between the collectively measures to protected constitutional fundamental rights and the Collective HC, as well as the proposal for its regulation, overcoming embalmed points of the individual HC. In the fifth chapter, the research analyzed the restrictions brought by the Superior Courts to the Collective HC, presenting the divergences regarding such limitations. It understood that its legitimacy should be expanded and it should protect all types of collective rights, especially through preventive Collective HC to guarantee the right to free speech of undetermined individuals. The Collective HC procedure, the application of procedural techniques to it (such as self-composition, procedural legal acts, pre-constituted evidence, structural process, jurisdiction, the parties, autonomous production of evidence, fluid recovery, collective enforcement, among others) were also analyzed. In the final considerations, it was presented the reflections about the direction of the Collective HC, relating it to democracy, criminology, ideology, and culture, and the new composition of the Brazilian Supreme Court. The conclusion was that the technical inconsistency arising from the lack of application of collective redress concepts may be linked to the ideology adopted by the main actors of the legal system.